Localised functions for coding over multipath channels - Yudhi Santoso. (2008)
With the advances in VLSI technology and digital signal processing algorithms, wireless communications have seen tremendous advances in recent years. In a wireless environment, multipath effects are the most important to be considered in the design of a transceiver. Orthogonal Frequency Division Multiplexing (OFDM) has been used as the basis for IEEE 802.11 - Wireless LAN standards. OFDM can completely eliminate the effect of intercarrier and intersymbol interference by dividing a signal with high symbol rates into many subcarriers with low symbol rates. Hence, OFDM has a desirable property of robustness against frequency-selective fading.